(untitled) (Annals of Medical Research, 2022)
Aim: This study investigated the potential role of chronic restraint stress (CRS) on spatial memory, recognition memory, brain-derived neurotrophic factor (BDNF) and acetylcholine (ACh) levels in young adult rats. Material and Methods: In the study, 16 female rats of 12 weeks old were used. Rats were divided into two groups as control and CRS (n=8). CRS was applied 5 hours a day for 21 days. Following the end of CRS, recognition memory of rats was evaluated with new object recognition test (NORT) and spatial memory was evaluated with Morris water maze (MWM) test. At the end of the study, rats were euthanized and hippocampal tissue homogenates were obtained. Hippocampal BDNF and ACh levels were determined by ELISA method. Results: Exposure to CRS did not significantly change the exploratory behavior and discrimination index of rats (p>0.05). In the test phase in which spatial memory was evaluated, CRS decreased the time spent in the target quadrant (p<0.01). There was no significant difference between days in the training phase. CRS significantly decreased BDNF level in hippocampus (p<0.05). Hippocampal ACh levels were not statistically significant (p>0.05). Conclusions: CRS weakened cognitive functions in rats. This effect was mainly accompanied by a decrease in hippocampal BDNF levels. Our findings point to the potential role of BDNF in understanding the molecular mechanism of CRS-induced cognitive impairment.